SYSTEMIC FUNCTIONAL GRAMMAR OF THEME-RHEME USED IN FOLKATIVE INSTAGRAM ACCOUNT - Helmie, Jauhar; Sumitra, Raina Gesthia (TELL - US JOURNAL, 2024)
Social media has become part of people’s lives which enables people to communicate, interact, or look for the information. Instagram often used as a platform which upload the latest news, all the news can get on instagram easily. One of the news platforms on instagram is Folkative. This study aims to find out the types of theme-rheme and the most frequently used of theme-rheme in folkative instagram account by Gerot and Wignell (1994). A qualitative descriptive design was applied in this study. The results showed the analysis of 40 captions containing several types of themes, there are 37 topical themes, 1 textual theme, and 2 interpersonal themes found in folkative instagram account. In topical themes, the unmarked topical theme is found 25 themes, and the marked topical theme are 12 themes. The most frequently used of theme-rheme in folkative instagram account is topical theme. Hopefully, the results will inform people about the analysis of theme-rheme.